Effects of seasoning on the chemical composition and sensory qualities of roasted pork meat (2012)
The effect of seasoning on the chemical composition and sensory quality of Wasted pork meat was carried out in this study. Carcass of a slaughtered pig and other seasoning materials (Maggi Crayfish, Knorr Chicken, Ajinomoto, and Suppy Maggi) were purchased from Ayetoro market to conduct this nutritional test. Parameters determined under the proximate analysis were moisture Content, crude protein, ether extract (fat), crude fibre, ash, carbohydrate, and mineral (calcium, iron, phosphorous, potassium and sodium ions) using the routine procedures of digestion, distillation and titration. For the sensory quality determination, the spiced meat samples were given to fifteen (15) untrained panelists to test the samples for colour, aroma, taste texture overall acceptability using 9point hedonic scale. There was significant, difference in the mean value of the carbohydrate content. (%) for the six seasoned park samples at the 1% level of confidence (F-value - 29.533). The test of homogeneity of variance showed a significant difference in the equality of variance for carbohydrate content (%) for the six seasoned pork samples at the 1% level of confidence with a Levene Statistics (LS) value of 9.071. With respect to the physical qualities of the meat products (colour and texture), meat sample treated with Maggi crayfish + Pepper rated highest (5.60 and 7.73 respectively) and for the taste qualities (aroma and taste), meat sample treated with Suppy Maggi + Pepper scored 9.73. For overall acceptability, meal sample, treated with Knorr Chicken + Pepper was rated highest (7.33). It was recommended that treatment of pork meal with Maggi crayfish and Pepper should be encouraged to improve the physical qualities of the pork meat products (especially colour and texture) in the diets of men.